The Consequences of Short-Time Compensation: Evidence from Japan - Takao Kato; Naomi Kodama (Institute of Labor Economics (IZA), 2019)
There is a growing body of evidence on the efficacy of Short-Time Compensation (STC), a subsidy to promote worksharing in a recession, in achieving its intended goal of curtailing layoffs and preventing a sharp rise in unemployment. However, very little is known about the consequences of STC for firm performance. We apply the Propensity Score Matching (PSM) with difference-in-differences methodology to unique data from Japan, a country known for its extensive use, and find that STC results in improved profitability. The improved profitability is further found to be achieved through sales growth without raising labor costs. We explore possible mechanisms behind the observed positive consequences of STC for sales and profits. Additional evidence tends to favor what the psychology literature calls "shared adversity"- worksharing promoted by STC facilitates supportive interactions among workers in the firm and strengthens commitment of workers to the firm, and thereby enhances goal alignment between workers and the firm as well as between coworkers. Such workers are more open to the firm's effort to increase sales/revenues without raising cost.
Keywords: J23; J65; J68; H25; 330; short-time work; short-time compensation; worksharing; employment adjustment; firm performance